The Quest for Excellence of Aklan Ten Outstanding Mentors in Mathematics: A Collective Case Study - Ibabao, Jerrame Beltran (Universitas Sarjanawiyata Tamansiswa, 2026)
This study investigated the professional characteristics, teaching practices, and journeys of the Aklan Ten Outstanding Mentors in Mathematics to understand what makes them exemplary educators. Despite extensive research on effective math teaching components like pedagogical content knowledge and differentiated instruction, gaps remain in integrating how personal motivations, professional journeys, and contextual challenges in rural Philippine settings shape enduring excellence. Using a collective case study design grounded in post-positivist and social constructivist perspectives, the research explored how these mentors inspire learners, apply creative instructional strategies, and navigate professional challenges. Three awardees were selected as subjects. Data were collected via semi-structured interviews, classroom observations, and document analysis over 10 months. Thematic analysis using in vivo coding revealed five key themes: (1) use of student-centered and engaging teaching strategies; (2) strong commitment to professional growth and leadership; (3) active involvement in mentorship and collaboration; (4) application of real-world contexts in teaching mathematics; and (5) culturally responsive and inclusive practices.The study concludes that excellent math teachers not only enhance student learning but also lead transformative practices within the profession. These findings explain the importance of institutional support for professional development, mentoring, and teacher recognition to sustain quality mathematics education and foster a culture of excellence and inclusivity in schools.